The loss or absence of minimal residual disease of <0·1% at any time after two cycles of consolidation chemotherapy in CBFB–MYH11‐positive acute myeloid leukaemia indicates poor prognosis. (25th June 2020) - Duan, Wenbing; Liu, Xiaohong; Jia, Jinsong; Wang, Jing; Gong, Lizhong; Jiang, Qian; Zhao, Ting; Wang, Yu; Zhang, Xiaohui; Xu, Lanping; Zhao, Xiaosu; Qin, Yazhen; et al.
Summary: No consensus has been reached on the relationship between CBFB‐MYH11 copies and prognosis. Of 1525 acute myeloid leukemia (AML) patients, 58 with CBFB‐MYH11‐positive AML (16/58 patients with c‐kit mutation) were retrospectively analyzed with a median follow‐up duration of 29.8 (range: 4.8–74.4) months. Of these, 25/58 (43.1%) patients underwent allogeneic hematopoietic stem cell transplantation (allo‐HSCT), 10 of whom had the c‐kit mutation. Of the 33 patients who did not undergo allo‐HSCT, recurrence in patients with CBFB‐MYH11/ABL level >0.1% at any time after two consolidation cycles was significantly higher than in patients with CBFB‐MYH11/ABL level <0.1% (61.9% vs. 0%, P = 0.001); further, the 3‐year relapse‐free survival (RFS; 31.4% vs. 100%, P = 0.004) and event‐free survival (EFS; 33.1% vs. 100%, P = 0.004) were significantly decreased in patients with CBFB‐MYH11/ABL level >0.1% at any time after two consolidation cycles. The 3‐year RFS and EFS rates were lower in patients who did not receive allo‐HSCT than in those who did (31.4% vs 84.6%, P = 0.000; 31.4% vs. 80.8%, P = 0.001). CBFB‐MYH11‐positive AML patients with CBFB‐MYH11/ABL level >0.1% at any time after two cycles of consolidation had poor prognoses, and allo‐HSCT could improve their survival.